Statistical properties of traffic based on BDS-tests for realizing system of intrusion detection and prevention in a telecommunications network - Смирнов, Алексей Анатольевич; Дрейс, Юрий Александрович; Даниленко, Дмитрий Алексеевич (Ukrainian Information Security Research Journal, 2014)
The paper presents the mathematical apparatus of statisticalanalysis based on the BDS- test to investigate theproperties of network traffic of various services and informationservices in determining the significance of differencesor match their characteristics. The obtained experimentalresults of the statistical properties of networktraffic using correlation analysis of time series confirm thetheoretical assumption that different types of traffic(HTTP, FTP, Skype traffic and streaming ) BDS- testresult gives different values that can be taken as referenceusing and improving mechanisms for monitoring networkactivity, including the implementation of a system forintrusion detection and prevention in telecommunicationsystems and networks.